ACCEPTANCE OF A SOCIALLY ASSISTIVE ROBOT IN DEMENTIA CARE. (16th November 2018) - Adams, A; Saint, S; Zamer, J; Dahlstrom, R; Hedin, D; Beer, J
Abstract: Assistive technology, such as robots, has the potential to support healthy aging of older adults with and without dementia. Cognitive and socio-emotional tasks can be supported by a robot in addition to its traditional role for physical tasks. The goal of this feasibility study was to determine initial interest, engagement, facilitators, and barriers to support persons living with dementia (PWD) through social interaction via a Socially Assistive Robot. Twenty-five persons participated: 10 family caregivers, 5 PWD, and 10 staff caregivers. Participants completed questionnaires and interacted with an Aldebaran NAO robot called Archie in six scenarios. Archie was programed to follow a series of defined interactions that the experimenter executed based on a participant's response. A semi-structured interview covered first impression, benefits, concerns, and ratings of overall usefulness per scenario as well as general closing questions. Interviews were transcribed and coded. Overall, caregivers (N=20) were very positive towards Archie for all six scenarios and thought that Archie was more beneficial than other technologies. Caregivers agreed on the order of usefulness: Reminders to stretch were rated most highly (89% of participants rated it as extremely useful), followed by dance and movement, engagement through social reminiscing and discussion of hobbies, stress reduction, and last by providing information such as the weather (still 55%). Paid caregivers thought that Archie would be most useful in individual rooms and expected resident acceptance. Family caregivers saw benefits in different environments and had mixed opinions about resident acceptance of Archie. A common theme was the desire for personalization.